PENINGKATAN HASIL BELAJAR SIFAT-SIFAT BANGUN DATAR DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - RIZA, RIZA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study was motivated by the importance of the material properties and a low flat wake of learning outcomes in class V Elementary School 25 West Pasaman Kinali because teachers have not been able to relate the lessons to everyday life. This study was conducted with qualitative and quantitative approaches graders research subjects V. The results concluded a class action in the first cycle success RPP 71.4%, the successful implementation of the activities of teachers 71.4%, 64.3% success of student activity, and the average value of learning outcomes of cognitive, affective, and psychomotor 69. As for the second cycle of success RPP 92.8%, the successful implementation of the activities of teachers 92.8%, 89.3% successful student activity, and the average value of learning outcomes of cognitive, affective, and psychomotor 81.8. This proves the second cycle an increase in learning outcomes.   Kata kunci: hasil belajar; sifat-sifat bangun datar; contextual teaching and learning